Pengaruh Minuman Sinbiotik dari Susu Kefir dan Konsentrat Bengkuang (Pachyrhizus erosus) terhadap Kadar Malondialdehid Jaringan Usus Tikus Hiperlipidemia - Aprillia, Viola; Utami, Rizki Fajar; Pramaningtyas, Miranti Dewi (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Intestinal tissue damage is one of the effects of increased reactive oxygen species (ROS) in hyperlipidemia. Cells damaged by hyperlipidemia experience changes in the biomarker malondialdehyde (MDA). The use of jicama extract and kefir alone has shown the ability to lower cholesterol levels. This study aims to determine the effect of the combination of jicama extract and kefir milk as a synbiotic drink on MDA levels in the intestines of hyperlipidemic rats. Methods Twenty-five male Wistar rats were divided into 5 groups, consisting of negative control (K-) and positive control (K+) groups and three treatment groups (P1, P2, P3). Hyperlipid induction using quail egg yolk. The dose of quail egg yolk was 5ml/200grBW. The intervention group was given a synbiotic drink with a dose of 5ml/200grBW with 3 types of kefir milk and jicama extract combination formulations. Intestinal MDA levels were measured after termination and the data were analyzed using statistical software. Results The level of MDA in intestine (nmol/ml) were 11.78±0.21 (K+), 0.73±0.05 (K-), 5.38±0.28 (P1), 3.02±0.14 (P2), 1.59±0.11 (P3). The analysis of the results of the MDA level showed significant differences in all groups after being given synbiotic drinks (p <0.001). Conclusions Combination of jicama extract and kefir as synbiotic drinks significantly affect the intestinal MDA levels of hyperlipidemic rats.